2015
DOI: 10.1177/0049475515587160
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with blood pressure control among patients attending the outpatient clinic of a South African district hospital

Abstract: Objective To determine the prevalence and factors associated with blood pressure (BP) control. Methods In a cross-sectional study involving 251 consecutively-sampled patients, a semi-structured questionnaire collected information on socio-demography, co-morbidities, hypertension treatments and BP control. Data analysis included descriptive statistics and logistic regression. Results Most participants were: on treatment for >5 years (60.6%); on three or more drugs (93.6%); treated according to guidelines (77%);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 15 publications
1
19
1
Order By: Relevance
“…The finding of prevalent suboptimal hypertension control in this study reiterates those of previous studies in South Africa and elsewhere, 4,5 and highlights the need to develop a scalable and sustainable intervention plan that targets factors that have been associated with poor BP control, including poor lifestyle behaviours (smoking, diet, alcohol, obesity, etc. ), weak social support network and high BOT as responsible factors.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The finding of prevalent suboptimal hypertension control in this study reiterates those of previous studies in South Africa and elsewhere, 4,5 and highlights the need to develop a scalable and sustainable intervention plan that targets factors that have been associated with poor BP control, including poor lifestyle behaviours (smoking, diet, alcohol, obesity, etc. ), weak social support network and high BOT as responsible factors.…”
Section: Discussionsupporting
confidence: 83%
“…3,4 Despite the availability of pharmacological treatments and access to health facilities, blood pressure (BP) control rates remain low globally and in South Africa only 24.5% -57.0% of patients with hypertension are reportedly controlled. 4,5,6,7,8,9,10,11 The reasons for poor BP control in sub-Saharan Africa are poorly understood and involve multiple, complex and varying factors depending on setting. 7 This often includes a high burden of treatment (BOT).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, little or no attention has been paid to laboratory assessment of hypertensive subjects and most of the required biomarkers of disease severity and progression are not routinely available in most health facilities in Nigeria. Studies of organ damage in subjects with hypertension showed that hypertensive heart disease, nephropathy, retinopathy, stroke, and ischemic heart disease are common even at the first contact in health care facilities [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However there have not been many studies that have evaluated clinic blood pressure control [16]. The utility of studying clinic based control lies in having the opportunity to work up patients for secondary causes and plan interventions.…”
Section: Introductionmentioning
confidence: 99%